عزالدین کے احوال و آثار - ڈاکٹر محمد نواز (FIKR-O NAZAR فکر ونظر, 2010)
Izzuddin, abd ul aziz ibn abd ussalam was a eminent scholar of 7th century of Syria and Egypt. He was inspired by Saif al din Al amidi. Many scholars consider him as the founder and the first and for most author for his work on the objectives of shriah as well as the commentator of the Holy Quran, mohaddith, motakallim, jurist, judge, preacher, reformer, mystic, law maker and embodiment of truth. He wrote many famous books on every Islamic studies topic. His writings on the Islamic teachings represent as guidance for the Islamic scholars in the succeeding centuries. This article will highlight his versatile scholarly life and will help the researchers to investigate about his seminal work.